Tuning Surface Wettability and Porosity of ZnO/Geopolymer Composite Membranes from Coal Fly Ash through H₂O₂ as Pore-Forming Agent - Rendy Muhamad Iqbal; Siswo Siswo; Erwin Prasetya Toepak; Hamzah Fansuri; Muhammad ‘Adli Nor Azman; Yusuf Wibisono; Sri Wardhani; Deni Shidqi Khaerudini (Helium: Journal of Science and Applied Chemistry, 2026)
The development of geopolymer membranes from industrial by-products offers a sustainable approach for water purification. In this study, ZnO/geopolymer membranes were prepared from coal fly ash, with hydrogen peroxide (H2O2) used as a pore-forming agent to regulate porosity and surface wettability. The influence of H2O2 concentration (0-6 wt%) on membrane physicochemical properties was systematically evaluated. FTIR analysis confirmed the formation of sodium aluminosilicate hydrate (N-A-S-H) gel and the incorporation of ZnO through the presence of Si-O-Zn and Zn-O bands. SEM images showed that increasing H2O2 concentration changed the initially dense structure into a rougher and more porous surface due to oxygen bubble generation during curing. ZnO addition enhanced surface roughness and functionality, while H2O2 improved pore connectivity. The water contact angle decreased from 21.63° in the pristine geopolymer to below 15° in the membrane with 6 wt% H2O2, indicating greater hydrophilicity. Porosity also increased from about 10% to 50%. These results demonstrate that ZnO incorporation combined with controlled H2O2 addition effectively tailors membrane wettability and pore structure, making the composite promising for sustainable water filtration.